PEMAMFAATAN LIMBAH BAKAU UNTUK PEMBUATAN AQUASCAPE SEBAGAI USAHA MIKRO DI DESA MATA AIR PESISIR SULAMANDA: UTILIZATION OF MANGROVE WASTE FOR AQUASCAPE MANUFACTURING AS A MICRO BUSINESS IN MAT AIR VILLAGE SULAMANDA COASTAL - Saraswati , Suprabadevi Ayumayasari; Toruan, Lumban Nauli Lumban; Rammang, Nixon; Namas, Benediktus Julio Ta (Jurnal Pengabdian Perikanan Indonesia, 2023)
Aquascape is one form of media that can be used for fish maintenance, especially ornamental fish for home scale. Aquascape itself is the identity of life that represents the original habitat of fish. Physically, the aquarium is only a place or container. Aquascape is the art of combining aquatic plants and ornamental fish in water media. However, the existing Aquscape products are generally large in size with expensive prices so that they can only be reached by large consumers such as hotels, restaurants, and offices. The use of mangrove waste is an alternative and also the use of natural materials that are environmentally friendly. Aquascape can meet the needs of the middle to lower market and accommodate the needs of office workers who do not have a large space or place to put an aquarium, so the mini Aquascape business becomes very promising. Some of the problems faced in presenting the natural atmosphere, starting from the fish that cannot survive to the dirty and mossy fish Aquascape quickly. By conducting training on making mini Aquascapes and fish rearing techniques, especially ornamental fish, it is hoped that it can provide information to coastal community fishermen to try to apply it to home micro scale. The method used is field observation, coupled with literature studies and socialization to fishermen on the Sulamanda coast.